Does Early Exposure to Chinese–English Biliteracy Enhance Cognitive Skills? - Yin, Jing; Guan, Connie Qun; Smolen, Elaine R.; Geva, Esther; Meng, Wanjin (Frontiers in Psychology, 2022)
Clarifying the effects of biliteracy on cognitive development is important to understanding the role of cognitive development in L2 learning. A substantial body of research has shed light on the cognitive factors contributing to biliteracy development. Yet, not much is known about the effect of the degree of exposure to biliteracy on cognitive functions. To fill this research void, we measured three categories of biliteracy skills (language, reading, and cognitive-linguistic skills in both Chinese and English) jointly and investigated the effects of biliteracy skill performance in these three categories on cognitive skills (working memory and attentional control) in Chinese L1 children who were exposed to English as L2 beginning at age 3 (“early”) or in grade 3 (“late”). In this cross-sectional study, 10 parallel Chinese and English language, reading, and cognitive-linguistic measures were administered to emerging Chinese-English bilingual children in grade 3 (n = 178) and grade 6 (n = 176). The results revealed that early exposure to Chinese-English biliteracy enhanced cognitive skills but with a cost of a slight delay in performance on Chinese L1 language skills in grade 3 (but not in grade 6). Importantly, the present findings suggest that, in addition to universal and developmental processes, the cumulative effect of early and sustained bi-scriptal exposure enhances working memory and attention in school children.